Taksonomi gaya pembelajaran dan tingkat motivasi pelajar dewasa - Hamdan, Abdul Rahim; Abdul Ghaffar, Mohamed Najib; Sihes, Ahmad Johari; Ramli, Jamaluddin (Faculty of Education, 2008)
The objectives of this study are to determine the taxonomy of learning style, and the study motivation of adult learner (PKPGB). A total of 321 second year PKPGB students from seven Malaysian Public Universities were involved in the study. The study also seeks to identify the differences of learning styles and study motivation among the PKPGB students. Questionnaires were used in this descriptive study to obtain the required information. Mean values and ANOVA test were used to analyse the data. Results showed that the deep learning style taxonomy is at the medium level (mean, 3.15), while the surface learning taxonomy is at the low level (mean, 3.00). The intrinsic study motivation taxonomy is at the low level (mean, 2.11), and the extrinsic study motivation is at the medium level (2.82). Overall, the PKPGB students’ academic achievement is at the medium level (CGPA, 3.38). There are no significant relationships between deep learning, surface learning and academic achievement. Results also showed that there is no significant relationship between intrinsic motivation and academic achievement, but significant relationship exists between extrinsic motivation and academic achievement. The study also revealed that there is a significant difference (α=0.001) in extrinsic motivation among the PKPGB students according to university. No significant differences were found in deep learning, surface learning and intrinsic motivation among the students. Based on the findings, it is concluded that the adult learners (PKPGB) pursue their study because of recognition and certification. Incentives should be rewarded in order to encourage the PKPGB students to utilise their experience and knowledge gained in their study to upgrade their competencies.